2016
DOI: 10.1590/1678-4685-gmb-2015-0178
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cell therapy promotes the improvement and recovery of renal function in a preclinical model

Abstract: Acute renal failure (ARF) is an extremely important public health issue in need of novel therapies. The present study aimed to evaluate the capacity of mesenchymal stem cell (MSC) therapy to promote the improvement and recovery of renal function in a preclinical model. Wistar rats were used as the experimental model, and our results show that cisplatin (5mg/kg) can efficiently induce ARF, as measured by changes in biochemical (urea and creatinine) and histological parameters. MSC therapy performed 24h after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…The early mechanism of MSCs may be due to the production of soluble factors, such as nitric oxide [47], indoleamine 2,3-dioxygenase (IDO) [48], hepatocyte growth factor (HGF) [65], and transforming growth factor-β [46]. Moreover they may also exert immunosuppressive functions through direct cell-to-cell contact.…”
Section: Mesenchymal Stem Cells As Therapeutic Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…The early mechanism of MSCs may be due to the production of soluble factors, such as nitric oxide [47], indoleamine 2,3-dioxygenase (IDO) [48], hepatocyte growth factor (HGF) [65], and transforming growth factor-β [46]. Moreover they may also exert immunosuppressive functions through direct cell-to-cell contact.…”
Section: Mesenchymal Stem Cells As Therapeutic Toolsmentioning
confidence: 99%
“…Some studies have suggested that MSCs have the innate ability to migrate to sites of inflammation and also to the tumor microenvironments. While all of the factors that contribute to MSC migration remain to be identified, research has suggested that MSC migration is caused by different chemokines and interplay with chemokine receptors, for example, stem cell factor (c-kit), HGF or c-Met [76], platelet derived growth factor (PDGF)/PDGF receptor [48,49], vascular endothelial growth factor (VEGF)/VEGF receptor [77], monocyte chemo-attractant protein-1 (MCP-1), C-C chemokine Type 2 receptors [46], high mobility group box 1, receptor for glycation end-products [78,79], stromal cell derived factor 1 (SDF-1), C-X-C chemokine Type 4 receptors (CXCR4) [47,48], as well as additional cell adhesion molecules (Fig. 2) [47,80].…”
Section: Mesenchymal Stem Cells As Therapeutic Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential of bone-marrow-derived MSCs to accelerate healing has been demonstrated in several rat models of hypertension (as discussed above) and of renal disease, including in the anti-Thy1.1 model (Li et al, 2006), the 5/6th nephrectomy model of progressive CKD (Cavaglieri et al, 2009; Choi et al, 2009) and in an AKI model induced by cisplatin (Urt-Filho et al, 2016). MSCs might reverse AKI by a paracrine mechanism rather than by MSC transdifferentiation.…”
Section: Models Of Acute and Chronic Kidney Diseasementioning
confidence: 99%
“…The differentiation medium was changed every 72 h [49,50], and the differentiation process lasted 14 days [51,52].…”
Section: Adipogenic Differentiationmentioning
confidence: 99%